Writing the 'self' into self-practice/self-reflection (SP/SR) in CBT: learning from autoethnography. (2019) - Chigwedere, Craig
Abstract: Self-practice/self-reflection (SP/SR) allows cognitive behavioural therapists (CBT) to self-experience the techniques they use clinically. However, it is difficult to find published first-hand accounts of CBT therapists' SP/SR experiences. This may be because CBT research is primarily positivist and objective, while SP/SR is intrinsically subjective. Borrowing from the principles of autoethnography may offer a subjectivist qualitative methodology, allowing CBT therapists to write up their SP/SR experiences as rich, first-hand research material, potentially impacting theory and practice. This novel personal case study of SP/SR borrows from autoethnography, adapting it to analyse the self-practice of the CBT model of worry, in order to understand my own experience of worry as well as the model itself. Key learning aims: (1) To develop an approach to the research that is applicable to first-hand SP/SR material. (2) To demonstrate how therapists can continue SP/SR practice post-CBT training. (3) To illustrate how, with the aid of autoethnographic principles, SP/SR practice can influence not only the practitioner's personal and therapist-self, but also theory development.